Discovery of a highly active anticancer analogue of cardamonin that acts as an inducer of caspase-dependent apoptosis and modulator of the mTOR pathway - Khaled bin Break, Mohammed; Hossan, Md Shahadat; Khooa, Yivonn; Chow, Sek Chuen; Wiart, Christophe; Bradshaw, Tracey D.; Collins, Hilary; Khoo, Teng-Jin (Elsevier, 2018)
Nineteen analogues of cardamonin were semi-synthesized and tested against A549 and HK1 cell lines. The analogues were fully characterized via IR and NMR analyses, while compound 19 (a Cu (II) complex of cardamonin) was further characterized via HRMS, ELEMENTAL ANALYSIS, TGA and UV-VIS spectroscopy. Results of the MTS cell viability assay showed that several derivatives possessed cytotoxic activities that were several-fold more potent than cardamonin. Compound 19 was the most potent analogue possessing IC50 values of 13.2 µM and 0.7 µM against A549 and HK1 cells, corresponding to a 5- and 32-fold increase in activity, respectively. Furthermore, the active analogues, especially 19, have generally demonstrated lower toxicity towards normal MRC5 cells. SAR analysis showed the importance of the ketone and alkene groups for bioactivity, while substituting cardamonin’s phenolic groups with more polar moieties resulted in activity enhancement. As part of the SAR study and further exploration of chemical space, the effect of metal coordination on cytotoxicity was also investigated, but it was only possible to successfully obtain the Cu (II) complex of cardamonin (19), and results showed that the metal ion enhanced activity. 19 was also able to significantly inhibit the migration of A549 and HK1 cells. Further studies have shown that the most active analogue, 19, induced DNA damage resulting in G2/M-phase cell-cycle arrest in both cell lines. These events further led to the induction of apoptosis by 19 via caspase-3/7 and caspase-9 activation, PARP cleavage and downregulation of Mcl-1 expression. Finally, 19 inhibited the expression levels of p-mTOR and p-4EBP1. These data indicated that 19 exerted its anticancer activity, at least in part, via inhibition of the mTOR signalling pathway.